Island Invasions by Introduced Honey Bees: What Can Be Expected for Puerto Rico and the Caribbean? - Ackerman, James D. (Frontiers in Ecology and Evolution, 2021)
Apis species are a major component of pollinator faunas in their native and introduced habitats. A widespread concern is that non-native Apis mellifera may have negative effects on native pollinators and on plant reproduction. This is based on the assumptions that natural communities are at capacity, resource competition structures communities, native pollinators are more effective pollinators of native species, yet A. mellifera are superior competitors. The latter two assumptions are often true, but evidence from the Neotropics indicates that tropical communities are not tightly structured, and the foraging flexibilities of native bees maintain their populations. Unfortunately, the less diverse and disharmonic biotas of islands may limit the buffering capacity of flexible behaviors. While few studies address these assumptions or the ecological and evolutionary consequences of A. mellifera to the flora and fauna of tropical islands, an accumulation of taxon-specific studies are suggesting that such effects run the spectrum from subtle and indirect to obvious and direct. A concerted research effort is needed to address the multitude of issues to develop strategies to ameliorate or enhance honey bee effects, or just let nature take its course.